The Impact of Climate Variability on The Livelihood Structure of Farmers Households and Patterns of Adaptation - Purboningtyas, Titis Pury; Dharmawan, Arya Hadi; Putri, Eka Intan Kumala (Sodality: Jurnal Sosiologi Pedesaan, 2018)
This research was aimed to 1) identify the livelihoods structure of farmers household; 2) identify the adaptive mechanism of farmers household (patterns of adaptation). The data were collected by survey method in two villages, Kalianyar and Krangkeng, Indramayu District. There was 90 respondents of farmers household taken by purposive, 40 respondents in Kalianyar and 50 respondents in Krangkeng. Both villages were selected because they are ecologically vulnerable, characterized by drought due to climate variability. This research used livelihoods structure calculation and descriptive analysis method. The results of study showed that farmers households in Kalianyar have a better income and saving capacity than Krangkeng farmers households. To respond the effects of climate variability, farmers households in both villages by using ecological, economic and social adaptation patterns. Adaptation patterns are carried out as a form of farmers household strategies to overcome the adverse effects of climate variability. The livelihood assets used by farmers household in both village greatly influences the ability of farmer household to implement adaptation strategies.